2021
DOI: 10.33429/cjas.12121.6/6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Government Expenditure on Economic Growth in Nigeria, 1970-2019

Abstract: This study investigates the impact of Nigerian government expenditure (disaggregated into capital and recurrent) on economic growth using time series data for the period 1970-2019. The paper employs Autoregressive Distributed Lag (ARDL) model. To ensure robustness of results, the study accounts for structural breaks in the unit root test and the co-integration analysis. The key findings of the study are that capital expenditure has positive and significant impact on economic growth both in the short run and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 66 publications
1
30
0
Order By: Relevance
“…A study [16] shows that increasing government expenditure accelerates economic growth in low-income countries in sub-Saharan Africa, which is in line with the result of the study. The findings of [14] revealed that capital expenditure has a positive and significant impact on economic growth both in the short run and the long run, while recurrent expenditure does not have a significant impact on economic growth both in the short run and the long run. According to [19; 20], it was demonstrated that capital spending had a positive and significant effect on economic growth in East Africa which consistent with study.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…A study [16] shows that increasing government expenditure accelerates economic growth in low-income countries in sub-Saharan Africa, which is in line with the result of the study. The findings of [14] revealed that capital expenditure has a positive and significant impact on economic growth both in the short run and the long run, while recurrent expenditure does not have a significant impact on economic growth both in the short run and the long run. According to [19; 20], it was demonstrated that capital spending had a positive and significant effect on economic growth in East Africa which consistent with study.…”
Section: Resultsmentioning
confidence: 96%
“…The findings of a panel data regression analysis conducted in eight districts/cities in Indonesia (Baten) from 2010 to 2017 reveal that government expenditure has a positive impact on economic growth [13]. The impact of government expenditure on economic growth in Nigeria from 1970 to 2019 was studied using an Autoregressive Distributed Lag (ARDL) model, and the study's findings revealed that government expenditure had a positive and significant influence on economic growth [14]. A research [15] examines how government spending influenced economic development in developed, developing, and underdeveloped nations from 1980 to 2012 using the unbalanced panel technique.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As for the Capital spending, though not all the studies show that it has growth-enhancing impact, recent literature has more evidence about this result, compared to the older literature (Romp, W. E. & Haan, J., 2005). Moreover, according to the estimation of the short and long-run dynamics about public spending and economic growth in Nigeria for 1970-2019, when ARDL model with structural breaks was used, capital spending impacted economic growth, which demonstrates Keynes's theory in Nigeria (Aluthge et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 92%
“…In the long run, the study observed that all variables exerted a significant influence on economic growth. In a related study [ 40 ], assessed the degree of the impact of government expenditure on growth in Nigeria. Accordingly, findings indicated evidence of a significant positive impact of government spending on growth both in the long and short run.…”
Section: Empirical Issues: a Brief Reviewmentioning
confidence: 99%